Halal and Thayyib Practices of Street-Food Vendors Surrounding Four Islamic Universities in Yogyakarta, Indonesia - Iqbal, Muhammad; Afifah, Yunita Nur (Unisia, 2025)
Indonesia’s campus food belt teems with street-food stalls that promise lawful (halal) and wholesome (thayyib) fare, yet little is known about how vendors actually enact these twin obligations. This study therefore explores whether micro-vendors around four Islamic universities in Yogyakarta convert doctrinal awareness into day-to-day practice. Using a qualitative case-study design, thirty owner-operators were purposively selected for semi-structured interviews, direct observation, and photo documentation conducted over a three-month field period. Data were openly coded, compared across cases, and displayed in matrices linking stated knowledge to observed behavior. Findings reveal a marked asymmetry: while most vendors articulate the legal meaning of halal, only one in eight comprehends the broader thayyib mandate. Seventy percent consciously avoid visibly unsafe inputs and eighty percent oversee preparation themselves, yet forty percent apply no formal criteria when purchasing raw materials, allowing cost and convenience to override quality checks. Economic pressure, limited laboratory access, and sporadic inspections further dilute compliance, illustrating a persistent knowledge–behavior gap. Vendors who personally handle cooking and who have received community training exhibit higher sourcing selectivity, suggesting that hands-on control and peer learning can translate awareness into consistent practice. The study enriches halal assurance scholarship by shifting attention from factories and consumers to informal micro-enterprises. It recommends fee subsidies, localized training, and transparent ingredient traceability as mutually reinforcing levers to align economic opportunity with religious and public-health imperatives.